2001
DOI: 10.1177/016224390102600404
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Climate Forecasts and Societal Decision Making: Challenges to an Emergent Boundary Organization

Abstract: The International Research Institute for Climate Prediction (IRI) was created in 1996 with an “end-to-end” mission to engage in climate research and modeling on a seasonal-to-interannual time scale and to provide the results of this research in a useful way to farmers, fishermen, public health officials, and others capable of making the best of the predicted climate conditions. As a boundary organization, IRI straddles the divides between the production and use of research and between the developed world and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
79
0
4

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(83 citation statements)
references
References 19 publications
0
79
0
4
Order By: Relevance
“…Others have also begun to explore such questions (Agrawala 2001;Carr and Wilkinson 2005;Mollinga 2008). Nonetheless, a recent comprehensive survey conducted under the auspices of the Overseas Development Institute (ODI) concluded that despite a broad consensus on the need for boundary work in strengthening science-policy dialogue in developing countries, there is no consensus on how boundary work is actually carried out, or on how its effectiveness can be improved (Jones et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Others have also begun to explore such questions (Agrawala 2001;Carr and Wilkinson 2005;Mollinga 2008). Nonetheless, a recent comprehensive survey conducted under the auspices of the Overseas Development Institute (ODI) concluded that despite a broad consensus on the need for boundary work in strengthening science-policy dialogue in developing countries, there is no consensus on how boundary work is actually carried out, or on how its effectiveness can be improved (Jones et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…From a knowledge systems perspective Cash et al (2003Cash et al ( , 2005 defend the need for producing salient, credible and legitimate scientific information in order to make it 'actionable climate knowledge' (Meinke et al 2006). Other contributions to this discussion include end-to-end systems (Agrawala et al 2001) and co-production of science and policy (Lemos and Morehouse 2005). These underlying narratives permeate much of the discussion around the production of climate science and information and its use in policy and decision-making contexts.…”
mentioning
confidence: 99%
“…After having studied the region's basic social structure, the IRI chooses the regions and partners it wants to be involved with (Agrawala et al, 2001). It focuses on its partners' climate risks management strategies and aims at strengthening them through the integration of climate risk management.…”
Section: Irimentioning
confidence: 99%
“…It focuses on its partners' climate risks management strategies and aims at strengthening them through the integration of climate risk management. "IRI participates in the transnational flow of technical knowledge and skills, usually along a gradient from North to South" (Agrawala et al, 2001). Their research and tools help address development and adaptation issues in developing countries (IRI, 2007).…”
Section: Irimentioning
confidence: 99%